(untitled) - Carlo Batini (Redwood City, California, 1992)
The book is divided into three parts. Part 1 examines conceptual design in detail including data modeling concepts, methodologies for conceptual design, and view design and integration. In part 2, the book discusses functional analysis and explains how to conduct joint data and functional analysis. Part 2 also includes a large, realistic case study designed to illustrate key database concepts and teach to solve design problems in a systematic way. Part 3 examines logical design and shows how to translate conceptual designs in the E-R model te the relational, network, and hierarchical models. It also addresses the problem of reverse engineering from these models to the E-R model. The book concludes with a chapter devoted to database design tools
Keywords: database design